Strategi Bank dalam Mempertahankan Loyalitas Nasabah pada Bank Muamalat Indonesia Kc Banjarmasin - Fattah, Abdul; MH, Masrina; Hasanah, Ikhwatun (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2024)
The study was motivated by MRI's research conducted at the end of 2021, which was announced during the 5th Infobank Satisfaction, Loyalty & Engagement (SLE) Award 2022. Bank Muamalat ranked first in Loyalty Index, Engagement Index, and Marketing Engagement. The achievement is credited to the efforts of Bank Muamalat KC Banjarmasin, which played a pioneering role in this accomplishment. This research is a qualitative study that uses both primary and secondary data. The subjects of the research are Branch Managers and Relationship Managers at Bank Muamalat Indonesia, Banjarmasin Branch. The research object is the strategies used by Bank Muamalat Banjarmasin Branch. Data collection techniques include observation, interviews, and documentation. The data analysis techniques used are Inductive and Grounded theory approaches. The results of the research show that the strategies used by Bank Muamalat to maintain customer loyalty involve several steps. Firstly, they select potential market segments that include Muslim customers with high religiosity and a good level of education. Next, Bank Muamalat always strives to maintain customer trust, provide the best services, and engage in intensive communication. Continuous evaluation and monitoring are also conducted to support efforts in maintaining customer loyalty, including assessing the usage of their products by customers, conducting customer satisfaction surveys, and utilizing surveys conducted by independent institutions. Keywords: Strategy, Loyalty, Bank Muamalat